Atomic scale behavior, growth morphology and magnetic properties of CoO on MgO(100) surface: a density functional study - Zayed, A.O.H.; Zain, Sharifuddin Md (Springer Verlag (Germany), 2016)
In this study, we investigated the adsorption behaviors of the Co atom and CoO molecules on the MgO(100) surface, including the diffusion processes based on density functional theory calculations. The structure and growth morphology of the deposited cobalt oxide at various coverage levels as well as the magnetic properties are also discussed. The CoO molecule is found to bind more strongly to the surface compared to the isolated neutral Co atom, which is physically adsorbed on top of the surface oxygen site. Different to the isolated Co atom, the diffusion path of CoO molecule predominantly involves 90° rotation movements about its ends, while the surface hollow site acts as the saddle point for the hopping of the Co atom between two adjacent oxygen sites. A two-dimensional growth mode is observed to be the dominant layer growth mechanism for CoO on the magnesia surface, where the antiferromagnetic state is energetically more favorable compared to the ferromagnetic state. Based on the charge transfer and the density of state distribution, the interaction with the magnesia substrate does not affect the magnetic properties of the CoO monolayer.